Quantitative analysis of inhibitor‐induced assembly disruption in human UDP ‐ GlcNAc 2‐epimerase using mass photometry - Boback, Nico (2025)
Uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) 2-epimerase (GNE)/N-acetylmannosamine kinase is the rate-limiting enzyme in sialic acid biosynthesis and a promising therapeutic target. We applied mass photometry (MP) to investigate GNE oligomerization and its modulation by three small-molecule inhibitors (C5, C13, and C15). Substrate-binding (UDP-GlcNAc) stabilized tetramer formation by increasing dimer–dimer affinity 98-fold. All inhibitors destabilized tetramers in a concentration-dependent manner, with IC 50 values in the low micromolar range. Using a modified Cheng–Prusoffuation, IC 50 values were converted into KB,app values. Schild analysis and Operational Model of Allosterically Modulated Agonism were applied to estimate an apparent KB,app value and assess cooperative inhibition effects. Molecular docking confirmed competitive binding for all inhibitors and helped rationalize observed potency trends. While MP has previously been used to study protein assembly, our work demonstrates its applicability for the label-free, quantitative characterization of small-molecule inhibitors affecting protein oligomerization. These findings provide a foundation for further mechanistic studies and underscore the potential of MP in drug-target interaction profiling.